Malignant rhabdoid tumour of liver: Conundrum on ascitic fluid. Issue 4 (14th February 2023) - Sharma, Rashim; Thirunavukkarasu, Balamurugan; Nalwa, Aasma; Pathak, Manish; Garg, Pawan Kumar
Abstract: Ascitic fluid analysis is an important tool for diagnosis and staging. Cytological analysis is routinely done as a part of workup for ascites. This is challenging in paediatric malignancies where multiple differentials need to be considered at times with limited cellularity. We present a case of malignant rhabdoid tumour of liver in a young child presenting with abdominal lump and ascites. The diagnosis was offered on ascitic fluid cytology based on cytomorphology, supporting immunohistochemistry and later confirmed on biopsy. This report briefly discusses its differentials and approach to diagnosis.